Fertilização nitrogenada, densidade de plantas e rendimento de milho cultivado no sistema plantio direto - de Brito Melo, Francisco; Cora, Jose Eduardo [UNESP]; Cardoso, Milton Jose (Univ Federal Ceara, Dept Geol, 2011)
In maize (Zea mays L.), the inadequate nitrogen supply and planting density are considered limiting factors to the grain yield. The objective of this study was to evaluate the influence of different nitrogen levels and plant densities to the maize yield components and productivity. The experiment was carried out in the Cerrado region, located in the southern of the Maranhao State, Brazil, in a clay Oxisol (Ustox), cropped under the no-tillage system for six years. The randomized completed blocks experimental design with four replications was used, with treatments arrangement in a 5 x 4 factorial. The treatments were a combination of five doses of nitrogen as urea (0, 50, 100, 150 and 200 kg ha(-1)) and four plant densities (25,000; 50,000; 75,000 and 100,000 plants he). The grain number and mass per spike and grain mass per plant were improved by increased N and decreased plant density. Higher incomes of grains were obtained with adding concomitantly in N doses and in plants density. The maximum grain yield (11,9 Mg ha(-1)) was obtained with 120 kg ha(-1) of N and 83,000 plants ha(-1).
Nitrogen fertilization, plant density and maize yield cropped under no-tillage system
Keywords: Corn; Plant-Nitrogen effect; No-tillage